Testing higher doses of sildenafil to repair brain injury secondary to birth asphyxia: an open-label dose-finding phase 1b clinical trial-sildenafil administration to treat neonatal encephalopathy-study 02 - Wintermark, Pia; Lapointe, Anie; Altit, Gabriel; Steinhorn, Robin; Rampakakis, Emmanouil; Meid, Andreas; Burhenne, Jürgen; Bajraktari-Sylejmani, Gzona; Khairy, May; Adamo, Marie-Therese; Gilbert, Guillaume; Toffoli, Daniela; et al. (The journal of pediatrics, 2025)
Objective - To evaluate the safety and tolerability of higher doses of sildenafil in neonates with hypoxic-ischemic encephalopathy (HIE) and brain injury. - Study design - A phase 1b open-label dose-finding clinical trial in neonates with moderate-severe HIE and confirmed brain injury on a day-2 magnetic resonance imaging during therapeutic hypothermia (TH). Enteral sildenafil was administered every 12 hours (q12 h) for 7 days. All participants received an initial dose 2.0 mg/kg, and a second dose of 2.5 mg/kg. Starting from the third dose, group 1 received 2.5 mg/kg q12 h and group 2 received 3.0 mg/kg q12 h. Primary outcome was incidence of dose-limiting toxicities. Secondary outcomes explored day-30 neuroimaging and 18-month neurodevelopment. - Results - Among the 30 neonates born between October 2019 and December 2021, 20 displayed day-2 brain injury and 13 received sildenafil (8 in group 1; 5 in group 2). In group 1, 25% (2/8) experienced transient hypotension after the first dose, linked to antiseizure medications. No significant hypotension occurred in group 2 when sildenafil was administered separately. At the 3.0 mg/kg/dose, steady-state sildenafil concentrations persisted beyond TH. Death or significant 18-month neurodevelopmental impairment occurred in 50% (4/8) of group 1 and 60% (3/5) of group 2. Among the survivors, partial recovery of brain injury was seen in 80% (4/5) of group 1 and 75% (3/4) of group 2; cerebral palsy developed in 0% (0/5) and 50% (2/4), respectively. - Conclusions - Enteral sildenafil up to 3.0 mg/kg q12 h was safe and well tolerated in a small single-center cohort of neonates with HIE treated with TH. Phase 2 trials are needed to assess multicenter feasibility and efficacy. - Trial registration - ClinicalTrials.gov NCT04169191.
Online verfügbar: 23. Juni 2025, Artikelversion: 14. Juli 2025
Gesehen am 08.12.2025